AKTIVITAS ASAP CAIR CANGKANG BUAH Hevea braziliensis SEBAGAI ANTI BAKTERI Staphylacoccus aureus - Widiya Agustina; Sumpono Sumpono; Rina Elvia (ALOTROP, 2017)
The aims of this research is to know the activity of liquid smoke Hevea braziliensis  Seed Shell as antibacterial of Staphylacoccus aureus. The synthesis of  liquid smoke on this research through some process such as pyrolysis, sedimentation, filtration, distillation and redistillation. H.braziliensis Seed Shell liquid smoke  obtained phenol levels 0.84% and pH  2.548. Antibacterial activity tested by hollow difusion methode with variations concentration of liquid smoke .at 5%, , 10 , 25 , 50, 75, and 100 % v/v. The effective concentration H.braziliensis  liquid smoke in inhibiting the growth of S. aureus bacteria is 75% v/v with strong antibacterial level that showed by an inhibition zone at 10,6 mm. On this research One Way ANOVA test showing the Fcount   ? F table, which means there is a significant difference between the diameter of the inhibition zone on various concentrations of H.braziliensis seed shell.iquid smoke..